2020
DOI: 10.24200/sci.2020.53357.3200
|View full text |Cite
|
Sign up to set email alerts
|

Multistage supply chain production–inventory model with collaborative preservation technology investment

Abstract: This paper investigates a multistage production-inventory model for deteriorating items, including raw materials and finished goods based on collaborative preservation technology investment. The major purpose is to determine the optimal materials supply, production delivery, replenishment and investment policies for the retailer and manufacturer in which the joint total profit of the integrated system is maximized. It uses mathematical programming analysis to ascertain the optimal solutions for the retailer an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…After that, they extended [19] by taking demand function is dependent on frequency of promotion and price in [20]. Recently, Chang et al [21] discussed a collaborative preservation technology investment-based supply chain model and shown that when considering the possibility of investing in collaborative preservation technology. Rahaman et al [22] discussed a green PI system with promotion of product, price and greenness influenced demand.…”
Section: Supply Chain Production-inventory Modelmentioning
confidence: 99%
“…After that, they extended [19] by taking demand function is dependent on frequency of promotion and price in [20]. Recently, Chang et al [21] discussed a collaborative preservation technology investment-based supply chain model and shown that when considering the possibility of investing in collaborative preservation technology. Rahaman et al [22] discussed a green PI system with promotion of product, price and greenness influenced demand.…”
Section: Supply Chain Production-inventory Modelmentioning
confidence: 99%
“…Chang et al [6] explored a production-inventory model with a multi-stage supply chain that uses preservation technology to prevent deterioration and boost investment. In the context of preservation technology investment, Kumar et al [21] determined the optimal policies for deteriorating artifacts.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In this research, developing a new approach based on the preservation-technology investment led to increase supply chain profit as well as reduce waste. Chang et al [11] developed a multi-stage deteriorating inventory model with considering preservation technology investment for maximizing the total profit. Yu et al [12] developed an inventory model for perishable products under carbon policy with considering preservation technology.…”
Section: Literature Reviewmentioning
confidence: 99%